Application of lean six sigma methodology to improve the weight inconsistency problem of coffee powder packaging - Nik Alimi Nik Aziz; Rosmaini Ahmad; Shaliza Azreen Mustafa; Tan Chan Sin; Muhammad Shahar Jusoh (Jurnal Sistem dan Manajemen Industri, 2021)
This paper presents a continuous improvement (CI) project based on the application of Lean Six Sigma (LSS) methodology. This project was carried out at coffee manufacturing industry located in northern area of Malaysia. The focus of this presented CI project is to improve the weight inconsistency problem of coffee powder packaging. The presented CI project was mainly guided with Six Sigma methodology of Define, Measure, Analyze, Improve and Control (DMAIC) steps, and related Lean tools applications. The step of Define summaries the overall view of CI project. In the step of Measure, current level of sigma based on defect per million of opportunities (DPMO) calculation was determined. Initially, 6% of rejected products were recorded, which it presents the sigma level at 3.1. In the step of Analyze, a series of team-based activities towards root cause identification was carried out. It included the applications of cause effect (CE) analysis and possible causes prioritization and close observations on packaging process. In the step of Improve, the related Lean tool was proposed to improve the problem under study. In the final step of Control, related supportive actions were suggested to sustain the effectiveness of the proposed solution. There are fourteen possible causes are initially identified in CE analysis and based on team’s evaluation process of possible causes prioritization four causes are collectively to be the most possible of root cause(s). Three close observation sessions were carried out to finalize the most possible root cause of the problem. Result strongly suggested that the high variation of coffee powder’s size and inconsistency is the root cause. An improvement strategy based on Lean Manufacturing approach called ‘poka yoke’ is proposed. The proposed improvement strategy was then validated based on real packaging process scenario. Result shows that the proposed improvement strategy is significantly effective to solve the problem with 0% of reject product was recorded so far, where it is not only produced the product within the acceptable weight of 215 and 208 grams, but also presents the reduction of weight fluctuation that close to ideal weight of 208 grams.